2010
DOI: 10.4049/jimmunol.1000101
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Induction of CCR9 on T Cells Requires Coactivation of Retinoic Acid Receptors and Retinoid X Receptors (RXRs): Exaggerated T Cell Homing to the Intestine by RXR Activation with Organotins

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 62 publications
2
31
0
1
Order By: Relevance
“…3). Furthermore, recent results from our laboratory indicated that RXR activation enhanced the RAR-dependent induction of CCR9 expression on naive CD4 + T cells, especially when RA levels were low (31). Thus, the expression of Rxra or Rxrb seemed to be required for the induction of RA responsiveness in naive T cells.…”
Section: Discussionmentioning
confidence: 90%
“…3). Furthermore, recent results from our laboratory indicated that RXR activation enhanced the RAR-dependent induction of CCR9 expression on naive CD4 + T cells, especially when RA levels were low (31). Thus, the expression of Rxra or Rxrb seemed to be required for the induction of RA responsiveness in naive T cells.…”
Section: Discussionmentioning
confidence: 90%
“…We showed previously that TBT and the RXR agonist PA024 enhance the RAR-dependent expression of CCR9 on naive CD4 + T cells and CD62L + naive-like nTregs, as well as their homing capacity to the small intestine upon activation (37). In the current study, we examined whether RXR agonists could also enhance the RAR-dependent modulation of Foxp3 + iTreg and Th17 differentiation.…”
Section: Ra Enhances Foxp3mentioning
confidence: 84%
“…high T cells were purified from splenocytes and lymph nodes (inguinal, axillary, brachial, and mesenteric), as previously described (1,37). Naive CD4 +…”
Section: Cd62lmentioning
confidence: 99%
See 1 more Smart Citation
“…This function is supported by the intestinal RA-producing CD103 + DCs through RARa and RARb but not RARg, whereas the activation of RXR enhances the effect but appears to be dispensable (34,51). In fact, the RA/RARa pathway directly controls the expression of the integrin subunit a4 (52).…”
Section: Ra In Innate Immunity Including Its Influence On Apcsmentioning
confidence: 99%